Evolution of the Product Manager. - CHISA, ELLEN (Communications of the ACM, 2014)
The article discusses the evolution of product managers' responsibilities. Topics discussed include the importance of product management in software development, coordination between product managers and engineers through the process of developing software, the need for the industry to push for better education designed for product managers, ways for product managers to develop their product management skills, reason why product management was not included in engineering curricula and advertising manager Neil McElroy's coinage of the term brand management.